E-Marketplace Penjualan Ikan Cupang Untuk Meningkatkan Potensi Daerah Berbasis Web - Candra Firstiyan Wijaya; Endang Supriyati; Tri Listyorini (Yayasan Literasi Sains Indonesia, 2023)
This E-Marketplace emerged from observing the problems that exist in the Betta Kudus community, namely the expansion of the sales sector and also the ease of making purchases. Betta fish sales that are currently being carried out are still using conventional systems and also through Facebook groups which are very ineffective because of the strict provisions on Facebook that prohibit the sale of live animals, so that many sellers who have uploaded their sales have been deleted by Facebook. This makes sales made by traders less than optimal. To solve the existing problems, a website-based application for selling betta fish was made. It is hoped that this application can be developed and useful for sellers and buyers of holy betta fish.